Contribution of Anaerobic Capacity to 100 Meter Sprint Performance in Karawang Athletics Athletes - Affrillia, Naswa; Rahmat, Willdan Demexsi; Amar, Muhammad; Setiawan, Muhammad Arief; Rahayu, Selvia (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
This study aims to analyze the relationship and contribution of anaerobic capacity to 100-meter sprint speed in track and field athletes in Karawang Regency. The study used a quantitative design with a correlational approach. The subjects consisted of 10 sprint athletes selected using a purposive sampling technique. Anaerobic capacity was measured using the Running-based Anaerobic Sprint Test (RAST) which produces indicators of peak power, mean power, and fatigue index, while sprint performance was measured through a 100-meter run test. Data analysis used the Pearson correlation test and simple linear regression. The results showed that peak power had a strong and significant negative relationship with sprint time (r = -0.71; p = 0.02), while mean power showed a moderate negative relationship (r = -0.65; p = 0.03). Fatigue index had a moderate positive relationship (r = 0.59; p = 0.04). Regression analysis showed that anaerobic capacity was able to explain approximately 50% of the variation in sprint performance (R² = 0.50). A sample size analysis using the G*Power approach demonstrated that the study's sample size met the minimum threshold for a correlation test with adequate test power. In conclusion, anaerobic capacity significantly contributes to 100-meter sprint performance. The practical implication of this study is the importance of training programs that focus on increasing explosive power and anaerobic capacity to enhance athlete performance.